LAW ENFORCEMENT AGAINST STREET CRIME (STUDY AT SOUTH TAPANULI POLICE) - Tona Simanjuntak; Rizkan Zulyadi; Wenggedes Frensh (SOSIOEDUKASI, 2026)
Street crime is a form of crime that often occurs in public spaces and disturbs the community, such as theft, mugging and violence on the street. This research aims to analyze the law enforcement efforts carried out by the South Tapanuli Police (Polres) in dealing with street crime and identify factors that become obstacles in the law enforcement process. The research method used is an empirical juridical approach, with data collection techniques through interviews, observation and documentation studies. The results of the research show that the South Tapanuli Police have taken various preventive and repressive steps, such as routine patrols, outreach to the community, and taking action against criminals. However, there are still several obstacles such as limited personnel, lack of community participation, and lack of operational support facilities. Therefore, synergy is needed between the police, local government and the community to create conducive security conditions. It is hoped that this research can provide input in formulating more effective policies in eradicating street crime in the area.